PEMANFAATAN SAMPAH DAUN ECENG GONDOK (Eichhornia crassipes) MENJADI BIOETANOL DENGAN PROSES FERMENTASI SEBAGAI SOLUSI ENERGI ALTERNATIF - Carlito Amaral (Jurnal Teknik Lingkungan, 2013)
Water hyacinth actually contains lignocellulose, while cellulose is a material for making paper, in addition to the content of cellulose, water hyacinth can also be used as materials for current bioethanol are necessary to address the decline of world oil production. Utilization of water hyacinth leaves of Swamp Dizziness aims to pile reduce and solids sediment as farmers or craftsmen utilizing water hyacinth rod as materials for furniture, where the leaves are directly discharged into the swamp so that will be a factor causing the silting marsh. Process manufacture of bioethanol through Phase Pretreatment (smoothing, filtering, hydrolysis (HCl 7%), heating and neutralization (NaOH 7%)), fermentation (Saccharomyces cerevisiae) and Distillation. Water hyacinth leaf litter samples containing ethanol after fermentation by yeast through the tape with a variety of yeast and fermentation time different levels of bioethanol produced after distillation to variations in the amount of yeast / yeast and fermentation duration variation sesbesar 41.07% in 9 days time variations with variations 20 grams of yeast, From the obtained results it can be concluded that the presence of variations in the number and length of fermentation yeast affect the levels of bioethanol produced. Elevated levels Best bioethanol fermentation occurs in 5-10 days with yeast added is 5% of the sample volume.